UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN MARKISA KUNING (Passiflora edulis var. flavicarpa degener) PADA BAKTERI Escherchia coli - Panji Ratih Suci; Latiful Fauziyah; Pramudita Putra Dwi Ramadhan (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2023)
Diarrhea is a condition in which the body loses most of its fluids and electrolytes caused by defecating three or more times a day with a thick, fluid consistency. The purpose of this study was to determine the antibacterial activity of the ethanolic extract of passion fruit (Passiflora edulis var. flavicarpa Degener) to inhibit the growth of Escherichia coli bacteria. The extraction method used maceration with 70% ethanol solvent and then continued with the antibacterial activity test at a concentration of 10%, 20%, and 30% using the disk diffusion method with 3x replication. The results of the antibacterial activity test were analyzed by the method of one-way ANOVA followed by a post hoc test (Tukey). The results of data analysis showed that the ethanolic extract of yellow passion fruit leaves had activity to inhibit the growth of Escherichia coli bacteria with the average diameter of the inhibition zone at a concentration of 10% (3.85 mm), at a concentration of 20% (6.61 mm), at a concentration of 30% (11.69 mm), and in the data analysis test, a value (sig 0.05) was obtained, which means that there are differences in the antibacterial activity of each concentration and positive control.